Positive compared with negative margins in a single-centre retrospective study on 3957 consecutive excisions of basal cell carcinomas. Associated risk factors and preferred surgical management. Issue 1 (February 2014) - Codazzi, D.; Van Der Velden, J.; Carminati, M.; Bruschi, S.; Bocchiotti, M. A.; Di Serio, C.; Barberis, M.; Robotti, E.
Abstract The rate of margins involvement and the associated recurrence risk in basal cell carcinomas (BCCs) varies widely in published works (7%–25% and 26%–67%, respectively). This study investigated the risk factors associated with incomplete excision and their relevance in surgical management when positive margins occur in 3957 BCCs excised in 2358 patients. This study performed a multivariate analysis on the database collected from all patients operated for BCCs in the Plastic Surgery Department between 1 January 1992 and 1 September 2007. All data collected (3957 excisions; 2358 individuals) were divided into complete and incomplete excisions groups and analyzed according to 14 variables. The overall rate of incomplete excisions was 14%. Mean age (68), size of the lesion (< 0.5 cm), BCC subtype (nodular with sclerosant aspects, sclerosant and basosquamous), location (face), infiltration depth (hypodermis and deep tissues), recurrent BCC and re-excised BCC were significantly associated with a higher rate of incomplete excision. The recurrence rate for incompletely excised tumours was 26.8%, while only 5.9% for completely excised tumours. Most of the risk factors associated to incomplete excision can be identified before surgery (by simple anamnesis and clinical examination) and successfully overcome by appropriate surgical margins. The high recurrence rate after incomplete excision and the low patient compliance towards follow-up should lead the surgeon to early re-excise residual cancer.